Pramoedya Ananta Toer's Buru Quartet literature as counter-hegemony and site of contestation in Indonesia's new order - Umali, Marie Bernardine A. (Asian Center, University of the Philippines Diliman, 2020)
In October 1965, Suharto's New Order government came into power through political violence and bloodshed, but gained hegemony by reinterpreting the country's history and the State ideology, the Pancasila, to promote authoritarian rule and repressing all competing narratives that stressed struggle. Among the works subjected to state censorship were Promoedya Ananta Toer's Buru Quartet historical novels. This study examines the reasons the New Order considered the novels, which focused on the realities of the Dutch East Indies, subversive. Using Antonio Gramsci's concept of hegemony and counter-hegemony as well as Benedict Anderson's concept of simultaneity, the study draws parallels between themes discussed in the Buru Quartet and the New Order realities. The study argues that these historical novels served as a counterhegemonic platform as they revolved around the struggles of groups including women, peasants, and ethnic groups that have been traditionally marginalized by an authoritarian and militaristic state. The narration of their experiences and the ideas articulated by the various characters in the novels contested the New Order ideologies that used Indonesia's past as one of its cultural and ideological resources. The study draws on historical information and context and undertakes a close reading of the text in order to identify the messages from the novel that would resonate with readers from New Order period and how thee messages work to undermine the hegemony set by the State to legitimize its rule".--Author